The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/15330338221148317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dose Calculation Based on Cone-Beam CT Using Different Measuring Correction Methods for Head and Neck Cancer Patients

Abstract: Purpose: To investigate and compare 2 cone-beam computed tomography (CBCT) correction methods for CBCT-based dose calculation. Materials and Methods: Routine CBCT image sets of 12 head and neck cancer patients who received volumetric modulated arc therapy (VMAT) treatment were retrospectively analyzed. The CBCT images obtained using an on-board imager (OBI) at the first treatment fraction were firstly deformable registered and padded with the kVCT images to provide enough anatomical information about the tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…The early approach for dose calculation on CBCT was using the planning CT (pCT) calibration curve or CBCT calibration curve, which could bring unstable outcomes 12,13 . It was reported that dose calculation based on a CBCT calibration curve could result in an accuracy of 1-5% [13][14][15] . An intensive technique is to replace the HU value of CBCT with the HU density or CT numbers of pCT [16][17][18] .…”
mentioning
confidence: 99%
“…The early approach for dose calculation on CBCT was using the planning CT (pCT) calibration curve or CBCT calibration curve, which could bring unstable outcomes 12,13 . It was reported that dose calculation based on a CBCT calibration curve could result in an accuracy of 1-5% [13][14][15] . An intensive technique is to replace the HU value of CBCT with the HU density or CT numbers of pCT [16][17][18] .…”
mentioning
confidence: 99%